The Scientific Output of Kerman University of Medical Sciences Iran in Web of Science - Maryam Okhovati; Azam Bazrafshan; Morteza Zare; Leila Abdollahi; Maliheh Sadat Bazrafshan (Kerman University of Medical Sciences, 2016)
Background & Objective: Publishing in journals indexed in wellknown indexes is the best way to present an article internationally It also illustrates the contribution of scholars to the advancement of knowledge in the world This study aimed to investigate the scientific output of Kerman University of Medical Sciences Iran in Web of Science (WOS) during 2004 to 2013 Methods: This applied research uses scientometrics and citation methods to investigate the scientific publications of Kerman University of Medical Sciences during 20042013 The data were gathered from Web of Science Results: During this time period researchers at Kerman University of Medical Sciences had published 1053 documents in WOS Most of the documents were in article format The growth rate of scientific contribution was 70% and the universitys Hindex was 30 The papers distribution followed the Lotkas law In total the papers had received 4619 citations Only 247% of papers were written by one author The studied researchers had the most collaboration with Tehran University of Medical Sciences among Iranian universities and the University of Amsterdam among foreign universities The fields pharmacy and pharmacology had produced the most papers Conclusion: The results indicated a growing trend in publications and high rates of scientific collaboration by Kerman University of Medical Sciences It is suggested that different departments follow the experience of departments with the most productivity in order to increase their output In this way all departments will contribute to the universitys scientific output Moroever new policies should be considered to increase the citation rate